2017
DOI: 10.4049/jimmunol.1700672
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Tissue Inflammation Promotes Increased Matrix Metalloproteinase-12 Production by CD200Rlow Monocyte-Derived Cells in Periodontitis

Abstract: Irreversible tissue recession in chronic inflammatory diseases is associated with dysregulated immune activation and production of tissue degradative enzymes. In this study, we identified elevated levels of matrix metalloproteinase (MMP)-12 in gingival tissue of patients with the chronic inflammatory disease periodontitis (PD). The source of MMP12 was cells of monocyte origin as determined by the expression of CD14, CD68, and CD64. These MMP12-producing cells showed reduced surface levels of the coinhibitory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 62 publications
3
24
0
2
Order By: Relevance
“…It is worth noting that the secreted levels in the cultures were somewhat similar to that of differentiated macrophages in monoculture. Our group previously reported that monocyte-derived cells in the model are CD64 + and display increased expression of CD14, CD68, and CD163 during their differentiation, evidencing a macrophage-like phenotype (20). Previous reports have shown that both TLR ligands and IFN-γ induce S100A12 expression in monocytes and/or macrophages (12,36,37).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…It is worth noting that the secreted levels in the cultures were somewhat similar to that of differentiated macrophages in monoculture. Our group previously reported that monocyte-derived cells in the model are CD64 + and display increased expression of CD14, CD68, and CD163 during their differentiation, evidencing a macrophage-like phenotype (20). Previous reports have shown that both TLR ligands and IFN-γ induce S100A12 expression in monocytes and/or macrophages (12,36,37).…”
Section: Discussionmentioning
confidence: 77%
“…A 3D oral tissue model was set up containing epithelial cells (TERT-immortalized normal human oral keratinocyte line OKF6/TERT-2, kindly provided by J. Rheinwald) (23), primary fibroblasts (24), and monocytes as previously described (20). Briefly, 3-µm pore size transwell inserts were placed in 6-well plates and coated with a mixture of bovine type I collagen (PureCol, Cell Systems, Troisdorf, Germany) and DMEM (GE Healthcare Life Sciences, Uppsala, Sweden).…”
Section: D Oral Tissue Culturementioning
confidence: 99%
See 1 more Smart Citation
“…MMPs are a family of Zn 2+ -containing neutral proteolytic enzymes that degrade extracellular matrix (ECM). Human MMPs are classified as collagenases, gelatinases, matrix lysins, membrane-type MMPs and other MMPs (14,15). The direct effects of MMPs in periodontal tissue destruction and degradation are involved in the development of periodontitis.…”
Section: Il-18 Promotes the Secretion Of Matrix Metalloproteinases Inmentioning
confidence: 99%
“…Показана можливість трансформації М1 фенотипу в М2 при зміні спектра стимулюючих цитокінів. Одна з відмінностей між М2 і М1 полягає в тому, що в М2 продуктами метаболізму аргініну є орнітин і поліаміни, тоді як у М1 -оксид азоту та цитрулін [5]. Доведено, що паралельне визначення показників експресії CD68 та індуцибельної ізоформи ферменту синтази оксиду азоту (iNOS) дає можливість оцінити поляризацію макрофагів у бік «класично» активованих М1 із значним утворення фактору некрозу пухлин-α, оксиду азоту та інших прозапальних цитокінів та медіаторів [6].…”
unclassified